SKRINING FITOKIMIA DAUN DAN BATANG CINCAU HIJAU ATAU DAUN DALUMAN (CYCLEA BARBATA MIERS) SEBAGAI TERAPI GASTRITIS - gasim soka, burhanudin (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Green grass jelly is a plant that is widely used by people as medicine or as food. One of the benefits of the green grass jelly plant is as a gastritis therapy. This is because the grass jelly plant contains various compounds such as alkaloids, saponins, tannins and flavonoids. The parts often used are leaves and stems. So the aim of this research is to prove the contents of the green grass jelly plant which are predicted to be a medicine for gastritis, so a phytochemical screening was carried out and differentiating the contents in the leaves and stems of the green grass jelly plant. The method used experimentally was making 96% ethanol extract of green grass jelly leaves, and screening for phytocia. The results showed that the 96% ethanol extract of leaves and stems contained alkaloids, saponins, flavonoids and tannins. The difference between leaves and stems is that there is no sediment but there is turbidity. The conclusion of the research is that the contents contained in the 96% ethanol extract of green grass jelly leaves and stems are the same, namely alkaloids, saponins, flavonoids and tannins.